Development of student worksheets based on Augmented Reality Sub Material Phases of the Moon to Increase Student Learning Motivation - Mela Mahardika Ilafi; Ragil Saputri; Sabar Nurohman; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to design and create teaching materials in the form of Student Activity Sheets based on Augmented Reality technology in the Moon Phases sub-material, in order to increase student motivation. The research design used is a Research and Development (R&D) type with a 4-D model consisting of four stages, namely, Define, Design, Develop and Desseminate. The subjects in this study consisted of 30 students of class VII MTs Negeri 1 Jember. The results of this study at the product feasibility level showed a kappa moment in terms of content feasibility, presentation feasibility, and language feasibility showing an average value of 0.81 with a very high eligibility category, which means that student worksheets can be used in school learning. Furthermore, the average result of the practicality level of Augmented Reality-based student worksheets products from the aspects of convenience, efficiency, and benefits is 0.83 for teachers and 0.83 for students with very high practicality categories. Thus the developed Augmented Reality-based Student Activity Sheets can help learning more efficiently and make students more interested and motivated to learn.